Traumatyczna pamięć Wacława Iwaniuka - Rydz, Agnieszka (Wydawnictwo Naukowe UAM w Poznaniu, 2011)
Although the term “trauma” has recently been a bit abused, it is very well justified with regard to the poetry of Wacław Iwaniuk. Literary transformation of the biography of the author of “The Mirror” (World War II soldier serving on the front, prisoner of war and liberator of concentration camps in Germany) is realised within the “autobiographic space” of Ph. Lejeune. The war trauma is revealed in Iwaniuk’s literary output in the flashes of memory. Persistent reappearance of war scenes has been conveyed by the poet in a series of oneiric images. The metaphor of “a wound” (P. Ricoeur, R. Nycz) refers also to the post-war experience of a political exile. Wacław Iwaniuk lived outside Poland since 1939 and in 1948 he settled in Canada where he stayed till his death in 2001.
Traumatic memory of Wacław Iwaniuk